Penentuan Return Saham Syariah dengan Arbitrage Pricing Theory (APT) melalui Pendekatan Vector Autoregressive (VAR) - Seftina Diyah Miasary (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2023)
Arbitrage Pricing Theory (APT) is a pricing model that can be used to determine the expected return of a security. It assumes that there is more than one factor affecting the expected return. The risk of APT is part of the sensitivity of macroeconomic factors to return security. The identification of factors that affect security returns is one of the most important stages of APT modeling. This is because the APT does not specify how factors affect the return on a security. One method that can be used to identify macroeconomic factors is Vector Autoregressive (VAR). An overview of the relationship between return security and macroeconomic factors analyzed using VAR by going through the stages of checking the stationary data, determining the optimal lag length, testing Granger causality between variables, estimating the VAR model and Portmanteau diagnostic test, compiling the APT equation and calculating the expected stock return from APT models. Based on the results of the study, we conclude that at a significance level of 5%, only INDF shares show Granger causality with macroeconomic factors, such as the BI rate, money supply, and world oil prices. Furthermore, the Arbitrage Pricing Theory (APT) model implies that the expected return on INDF stock is lower than the actual return. This means that INDF's stock is undervalued, which means that future stock returns will be lower. Keywords: Vector Autoregressive (VAR), Arbitrage Pricing Theory (APT), Syariah Stock Return